Diversity and cellulolytic activity of cellulase-producing bacteria isolated from the soils of two mangrove forests in Eastern Thailand - TANAPAT BAMRUNGPANICHTAVORN; SUNISA UNGWIWATKUL; PARIMA BOONTANOM; AIYA CHANTARASIRI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Bamrungpanichtavorn T, Ungwiwatkul S, Boontanom P, Chantarasiri A. 2023. Diversity and cellulolytic activity of cellulase-producing bacteria isolated from the soils of two mangrove forests in Eastern Thailand. Biodiversitas 24: 3891-3902. The Southeast Asian countries hold the largest proportion of the world's mangrove area. Mangrove forests are a potential source for the isolation of economic microbial enzymes. Cellulases are a widely used microbial enzyme for cellulose degradation in various industries. Therefore, this study aimed to isolate, genetically identify, and enzymatically characterize cellulase-producing bacteria from the soils of two mangrove forests in Eastern Thailand. Twenty-six cellulase-producing bacteria were isolated and subsequently genotyped by Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) analysis of the 16S rRNA genes. Thirteen different RFLP patterns were obtained and genetically analyzed into six bacterial genera comprising Aeromonas, Bacillus, Chryseobacterium, Lysinibacillus, Pseudomonas, and Vibrio. The Bacillus species were the predominant cellulase-producing bacteria in the study sites. Moreover, the cellulase-producing Chryseobacterium and Lysinibacillus had hardly ever been reported. The Bacillus sp. strain RY08B was the most active cellulase-producing bacterium with 1.510±0.060 U/mL of CMCase activity. The optimum temperature and pH for the CMCase activity were determined to be 50°C at a pH of 7.0 with a thermal stability range of 25-50°C at a pH of 7.0. This bacterium could be applied in several environmentally friendly industries requiring mild conditions for their production processes.